Monday

December 22, 2014

December 22, 2014

Posted by **liza** on Tuesday, January 4, 2011 at 4:58pm.

- math -
**MathMate**, Tuesday, January 4, 2011 at 7:05pmFor a geometric series,

the nth term is

t(n)=ar^{n}

So

t(3)=ar³

t(6)=ar^{6}

t(6)/t(3)

= ar^{6}/ ar³

= r^{6-3}

= r³

Solve for r in

r³=9375/(-75)

r=(-125)^{1/3}

=-5

A = t(3)/r³

= -75/(-5)³

= 3/5

and first term

= t(1)

= Ar

= 3/5(-5)

= -3

**Answer this Question**

**Related Questions**

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Math - A sequence is formed by adding together the corresponding terms of a ...

maths - the third term of a geometric sequence is 6 and the sixth term is 3 over...

Math - 1. What is the tenth term of the geometric sequence whose first term (a1...

Math - The third term of a geometric series is 24 and the fourth term is 36. ...

someone explain to me! - the third term of a geometric sequence is t3= -75 and ...

math - in a certain geometric sequence, the third term is 8 and the sixth term ...

math - in a certain geometric sequence, the third term is 8 and the sixth term ...

Math - 3,5,-5... The first term in the sequence of #'s shown above is 3. Each ...

Math Algebra - The first term of a geometric progression is more than the third ...